Ethical Evaluation of Pharmaceutical Marketing in Pakistan - Ahmad, M.; Akhtar, N.; Awan, M. H.A.; Murtaza, G. (Acta Bioethica, 2011)
Our aim in this study is to give a broad overview of the main ethical and legal challenges of pharmaceutical market- ing. The purpose of this study was also to investigate unethical pharmaceutical marketing, the effect on physicians of receiv- ing gifts, the influences of perceptions regarding the importance of ethics and social responsibility on ethical intentions of marketing professionals. It also investigates the effect of unethical marketing on ultimate consumer (patient). Questionnaire based survey study was conducted from two main categories: (i) physicians/consultants and (ii) pharmaceutical companies. In Pakistan, there is no mechanism to monitor the drug promotional campaign by pharmaceutical industry despite the fact that there is enough evidence that irrational pharmacotherapy is increasingly encountered even in the developed countries due to unethical practices of pharmaceutical promotion. Medical practitioners and the pharmaceutical industry serve inter- ests that sometimes overlap and sometimes conflict. There is strong evidence that associations between industry and physi- cians influence the behaviour of the latter in relation to both clinical decision making and ethical promotion of drugs. The basic principles underlying the conduct of physicians with respect to pharmaceutical companies should be openness and transparency.